A General Outlook to Regenerative Pulp Therapy - Elif Sungurtekin Ekçi (Cumhuriyet Dental Journal, 2017)
Withing the last 10 years, the research regarding stem cell biology and tissue engineering has reaped many rewards in the field of dentistry. The goal of regenerative endodontic therapy is the regeneration of a healthy and functional pulp-dentin complex. With the development of successful materials such as mineral trioxide aggregate (MTA) and the use of the concept of tissue engineering, treating necrotic immature permanent teeth and stimulating the continuation of root-surrounding tissue formation has been made possible. Current stem cell research has also shown promising results and continues to show progress in the regeneration of dental and surrounding tissue. Since the ethical aspect of the use of stem cells is still in question, we have yet to see the potential of these materials in clinical practice. In this review, regenerative endodontic treatment prodedures, materials and developments are discussed in detail.